2019
DOI: 10.1111/jpc.14502
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners' perceptions of the ASQ‐TRAK developmental screening tool for use in Aboriginal children: A preliminary survey

Abstract: Aim:To determine health practitioners' experience of using the culturally adapted Ages and Stages Questionnaire -Talking about Raising Aboriginal Kids (ASQ-TRAK) and the Ages and Stages Questionnaire-3 (ASQ-3) with Australian Aboriginal families and their perception about parents' acceptability and understanding of the instruments. Methods: We surveyed a convenience sample of practitioners who had used both the ASQ-TRAK and the ASQ-3 developmental screening tools with Aboriginal children in the Northern Territ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…However, this was an unexpected result, as prior work exploring practitioners' perceptions of the ASQ-TRAK in similar settings, found that staff rated the ASQ-TRAK to be significantly more engaging than the ASQ-3 for Aboriginal families. 15 A relevant factor that might explain this difference in our study is that while Aboriginal Cultural Consultants administered the majority of ASQ-TRAK questionnaires in urban and regional centres this did not occur in the remote sites. In these sites non-Aboriginal outreach child health nurses, not from the community, were responsible for administering the ASQ-TRAK.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, this was an unexpected result, as prior work exploring practitioners' perceptions of the ASQ-TRAK in similar settings, found that staff rated the ASQ-TRAK to be significantly more engaging than the ASQ-3 for Aboriginal families. 15 A relevant factor that might explain this difference in our study is that while Aboriginal Cultural Consultants administered the majority of ASQ-TRAK questionnaires in urban and regional centres this did not occur in the remote sites. In these sites non-Aboriginal outreach child health nurses, not from the community, were responsible for administering the ASQ-TRAK.…”
Section: Discussionmentioning
confidence: 71%
“…Caregivers were surveyed about their ASQ‐TRAK experience. The survey (Appendix S1, Supporting Information) was adapted from a practitioners' survey 15 . It included nine questions, scored using a 5‐point Likert rating scale, which addressed the ease, acceptability and overall satisfaction, and interest in future screens using the ASQ‐TRAK.…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 presents an overview of studies included in this review. Of the 13 studies, nine were undertaken in Australia [ 13 , 17 , 18 , 19 , 20 , 22 , 23 , 25 , 27 ], two in the United States of America (USA; [ 21 , 24 ]), one in Canada [ 26 ], and one in Peru [ 11 ]. Eight studies were cross-sectional, two were qualitative, and three were mixed methods.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated the Ages and Stages Questionnaires: Talking About Raising Aboriginal Kids (ASQ-TRAK; [ 18 , 19 , 20 , 25 , 27 ]), three evaluated the Ages and Stages Questionnaires Third Edition (ASQ-3; [ 11 , 24 , 25 ]), one evaluated the Ages and Stages Questionnaires Second Edition (ASQ-2; [ 26 ]), one evaluated the Parents’ Evaluation of Developmental Status [ 22 ], one evaluated the Brigance Screens [ 13 ], one evaluated the Parents’ Evaluation of Listening and Understanding Measure (PLUM; [ 23 ]), one evaluated the Hearing and Talking Scale (HATS; [ 17 ]), and one evaluated the Survey of Well-being of Young Children (SWYC; [ 21 ]). The majority of identified screening tools were universal developmental screening tools, with the two exceptions being PLUM and HATS which are specific domain screeners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation